Effect of Land Cover Change on Discharge in Pangkajene Watershed - Rizki Amaliah; Usman Arsyad; Samuel A Paembonan (Fakultas Kehutanan, Universitas Hasanuddin, 2020)
Land cover changes that occur impact on the hydrological conditions in a watershed. The hydrological condition referred to as the output quantity of the watershed is discharge which describes the quantity of water. This study aims to determine the effect of land cover change on streamflow in the Pangkajene Watershed. The results showed that there was a decrease in average peak discharge in January of 213.73 m3/s to 95.79 m3/s in the same month in 2017. Land cover changes that occurred were mixed dryland farming of bushes into paddy fields, shrubs, and settlements while forests was experienced a slight change to open land by 0.69 ha. The increase in the area of paddy fields and shrubs as large as it causes the average discharge to decrease. A decrease in the average monthly discharge in the Pangkajene watershed due to rainfall on its way into the rice irrigation water experienced process begin from, is accommodated, evaporates, so that the flow up to the river becomes small. In addition, rainfall in 2009 which is the input of the Pangkajene watershed is higher than in 2017.